IMPLEMENTATION OF MULTIMEDIA LEARNING MODULE ON LEARNING ACHIEVEMENT TO ENHANCE STUDENTS' UNDERSTANDING OF TAWHEED - Rahmah, Rahmah; Yadiannur, Mitra (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
The concept of monotheism is the fundamental and most important element in Islam. This research aims to investigate the influence of multimedia learning modules on students' learning outcomes in enhancing their understanding of Tawheed by assessing the effectiveness of multimedia learning modules in improving students' understanding of monotheism. The research method employed was an experimental study involving three groups: one experimental group and two control groups. The population for this study consisted of all civil engineering and geology students, with 25 participants in each group, both in the experimental and control classes within the D-III Civil Engineering program. The sampling technique used was cluster random sampling. The research design utilized a Pretest-Posttest Mixed Design. Data analysis was conducted using the ANOVA Mixed Design in the General Linear Model (GLM) with the assistance of SPSS. The research findings indicate that the pretest-posttest score change in the experimental group is significant, with a Mean Difference (MD) of -27.850, as well as in the control group with a Mean Difference (MD) of -19.850. These score changes indicate that the Multimedia Learning Module can enhance students' understanding of Tawheed. The effectiveness of the Multimedia Learning Module in improving students' understanding of Tawheed is 0.839.